The Relationship between Characteristics of Pregnant Women and Level of Anxiety before Caesarean Section Surgery In Spinal Anesthesia At RSIA Abby Lhokseumawe - Millizia, Anna; Iqbal, Teuku Yudhi; Fajar, Ath Thahirah Annisa; Rizaldi, Muhammad Bayu (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2024)
Anxiety is a feeling of an uncomfortable that arises due to fear of something unspecified and unknown sources. The process of cesarean section surgery can induce anxiety, associated with fears of the surgical procedure, injections, the threat of death, and anesthesia. This can also encompass concerns about potential disabilities or death for both the mother and the baby. Factors such as age, level of education, and prior surgical experience in mothers can influence the level of anxiety before undergoing cesarean section surgery. This research aims to determine the relationship between the characteristics of pregnant women and the level of anxiety before cesarean section surgery with spinal anesthesia at RSIA Abby Lhokseumawe. The research method used is analytical with a cross-sectional approach. The research sample consists of patients who will undergo cesarean section surgery, with a total of 52 respondents. Sampling is done through purposive sampling. Data collection is carried out through interviews and questionnaires using the Amsterdam Preoperative Anxiety and Information Scale. The research results indicate that there is a relationship between the characteristics of pregnant women and the level of anxiety before cesarean section surgery with spinal anesthesia. The p-value for age data is 0.003, for education data is 0.001, and for surgical experience data is 0.000. This study found that the age, educational level, and prior surgical experience of pregnant women are associated with the level of anxiety before undergoing cesarean section surgery with spinal anesthesia.